Cavity partition and functionalization of a [2+3] organic molecular cage by inserting polar PO bonds. Issue 59 (29th June 2016) - Feng, Genfeng; Liu, Wei; Peng, Yuxin; Zhao, Bo; Huang, Wei; Dai, Yafei
Abstract : The cavity of a [2+3] organic molecular cage was partitioned and functionalized by inserting inner-directed PO bonds, which shows CO2 capture and CH4 exclusion due to the size-matching and polarity effects. Abstract : The cavity of a [2+3] organic molecular cage was partitioned and functionalized by inserting inner-directed PO bonds, which shows CO2 capture and CH4 exclusion due to the size-matching and polarity effects. Computational results demonstrate that the successful segmentation via polar PO bonds facilitates the CO2 molecules to reside selectively inside the cavity.